Metastatic signet-ring cell carcinoma of unknown primary origin. Issue 2 (April 2014) - Gregoire, C.; Muller, G.; Machiels, J.-P.; Goeminne, J.-C.
<x content-type="archive" xml:space="preserve">Abstract</x> About 3–5% of metastatic cancers originate from an unknown primary origin. Some have a signet-ring cell (SRC) component. We report the medical history of three patients with SRC carcinoma expressing both the oestrogen (ER) and progesterone receptors (PR). Although no primary breast cancer could be identified, we considered these three patients as having metastatic breast cancer. All of them were therefore treated with standard breast anti-hormonal therapies and all demonstrated benefit. The pitfalls of clinical presentation, diagnostic work-up, and treatment are discussed.